2021
DOI: 10.51668/bp.8321107s
|View full text |Cite
|
Sign up to set email alerts
|

Abuso cibernético en el noviazgo y relación intrafamiliar en adolescentes estudiantes mexicanos

Abstract: El alcance de la tecnología ha permitido que comportamientos abusivos en las relaciones de noviazgo sean vividos a través de medios electrónicos e internet. El objetivo del estudio fue determinar la existencia de asociación entre el abuso cibernético en el noviazgo (ACN) y la relación intrafamiliar (RI) en adolescentes estudiantes mexicanos ajustada por sexo, consumo de alcohol y violencia cara a cara en el noviazgo. Participaron 394 adolescentes con edades de entre 15 y 18 años (62,4% mujeres). Se encontró qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
1
4
1
3
Order By: Relevance
“…These results confirm the findings of other re-search works, where girls exercise more control violence [ 8 , 19 , 22 , 27 , 43 , 53 ]. The results differ with those obtained by other authors, who found that these types of behaviors were more unequally used, finding greater victimization in girls [ 36 , 51 , 54 , 55 ] and with other studies that concluded that such violence was used by both boys and girls in a similar way [ 9 , 24 , 56 , 57 , 58 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results confirm the findings of other re-search works, where girls exercise more control violence [ 8 , 19 , 22 , 27 , 43 , 53 ]. The results differ with those obtained by other authors, who found that these types of behaviors were more unequally used, finding greater victimization in girls [ 36 , 51 , 54 , 55 ] and with other studies that concluded that such violence was used by both boys and girls in a similar way [ 9 , 24 , 56 , 57 , 58 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Through the results, we can observe that more than a third of the respondents claim to have received controlling violence from their partner, and a little less than that third of the sample, reports having exercised, on some occasion, some type of controlling violence, especially when this is mainly carried out through mobile devices. These results confirm those obtained by various authors who have investigated this prevalence, placing it in similar ranges, although slightly higher than those obtained in this research [ 7 , 8 , 9 , 42 , 44 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In terms of gender, the results reported by previous studies are far from conclusive. Some found higher rates of cybervictimization among girls (Burkle et al 2011;Sourander et al, 2010;Zweig et al, 2013), whereas others claimed that boys suffer from cyberviolence more frequently than their female counterparts (Donoso et al, 2017;Piquer et al, 2017), and also perpetrate it more often (Buelga et al, 2010;Calvete et al, 2010;Durán & Martínez, 2015;Gabarda et al, 2021;Javier-Juárez et al, 2021). Other studies, however, failed to find any significant differences between boys and girls (Bennet, et al 2011;Didden et al, 2009), reporting that both perpetrate and suffer from dating cyberviolence in equal measure.…”
Section: Introductionmentioning
confidence: 99%